Post-truth, the Print Media and Political Messages in Ghana - Coker, Wincharles; Afriyie, Francis (Covenant Journal of Communication, 2019)
Post-truth is a regular component of electioneering campaigns and political discussions among politicians in sub-Saharan Africa. This regularity and dearth of literature have made the concept attractive to researchers who are interested in exploring its intricacies. This article examines the post truth strategies adopted by Ghanaian politicians of the two leading parties in their politically aligned newspapers -The Daily Statesman and The Enquirer. Three strategies were detected, namely kairos, disinformation/misinformation and strategic transmission of lies. By strengthening their gatekeeping performance through close examination and vetting of political statements before publishing them, newspaper editors stand the chance of moderating post truth politics and its attendant notoriety on the political scene of Ghana.